ANALISIS KEJAHATAN DENGAN MODUS PERAMPASAN SECARA PAKSA (STUDI KASUS KEJAHATAN JALAN DI WILAYAH HUKUM POLRESTABES SURABAYA) - Rise Sandiyantanti (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2015)
This study discusses the problem of Criminal Theft Mode by forcibly deprivation which becomes the "favorite" of the theft perpetrators in launching the action. Every person's behavior patterns including thieves reflect an intent or purpose, as well as his choice to commit a theft crime by forcibly seizing. This study was analyzed using descriptive analysis, which has been interviewed with a number of members of Surabaya Polrestabes police unit and some victims of theft by forcibly depriving them. The results show that (1) The modus operandi of this seizure becomes the "favorites" of the perpetrators to launch their crimes. This is because the implementation of the action is considered more efficient and easy. The threat mode as well as the rapid movements that make the victim unaware of the eventual theft will make the perpetrator immediately run away. (2) The modus operandi of criminal theft by force on the street is done by the perpetrator stalking the victim and if against it then it is scratched with a sharp weapon. Curus mode is often especially for teenagers who use vehicles or luxury goods that perpetrators do more than 1 person then forcibly take the property of the victim.